Detecting Ground Level Enhancements Using Soil Moisture Sensor Networks. Issue 8 (10th August 2021) - Hands, A. D. P.; Baird, F.; Ryden, K. A.; Dyer, C. S.; Lei, F.; Evans, J. G.; Wallbank, J. R.; Szczykulska, M.; Rylett, D.; Rosolem, R.; Fowler, S.; Power, D.; et al.
Abstract: Ground level enhancements (GLEs) are space weather events that pose a potential hazard to the aviation environment through single event effects in avionics and increased dose to passengers and crew. The existing ground level neutron monitoring network provides continuous and well‐characterized measurements of the radiation environment. However, there are only a few dozen active stations worldwide, and there has not been a UK‐based station for several decades. Much smaller neutron detectors are increasingly deployed throughout the world with the purpose of using secondary neutrons from cosmic rays to monitor local soil moisture conditions (COSMOS). Space weather signals from GLEs and Forbush decreases have been identified in COSMOS data. Monte Carlo simulations of atmospheric radiation propagation show that a single COSMOS detector is sufficient to detect the signal of a medium‐strength (10%–100% increase above background) GLE at high statistical significance, including at fine temporal resolution. Use of fine temporal resolution would also provide a capability to detect Terrestrial Gamma Ray Flashes (via secondary neutrons) which are produced by certain lightning discharges and which can provide a hazard to aircraft, particularly in tropical regions. We also show how the COsmic‐ray Soil Moisture Observing System‐UK detector network could be used to provide warnings at the International Civil Aviation Organization "Moderate" and "Severe" dose rate thresholds at aviation altitudes, and how multiple‐detector hubs situated at strategic UK locations could detect a small GLE at high statistical significance and infer crucial information on the nature of the primary spectrum. Plain Language Summary: Space weather events can lead to significant increases in the intensity of the atmospheric radiation environment, including at ground level. These ground level enhancements (GLEs) have been detected by a global network of neutron monitors for over 70 years. However, these instruments are expensive to construct and maintain. Only a few dozen are currently active, with no station located in the United Kingdom for several decades. As part of an effort to improve the resilience of UK infrastructure to space weather, we have studied the possibility of using alternative detectors to supplement neutron monitor measurements. COSMOS detector networks in the United Kingdom, North America, Australia and elsewhere use variations in ground level neutron flux to infer information on local soil moisture conditions for hydrological applications. We show that these same detectors could be dual‐purposed to provide information on GLEs that would complement the global neutron monitor network by providing much finer spatial resolution and, therefore, a highly localized warning system for space weather threats to aviation. Key Points: Data from cosmic ray neutron sensor (CRNS) networks have been reprocessed and analyzed in the novel context of Space Weather Ground level enhancements from solar cycle 24 present weak signals in the data Monte Carlo simulations show such CRNS networks are suitable for dual‐purposing as space weather detectors